Prevalence and predictors of occupational burnout among first-year medical residents in Oman: the role of trait emotional intelligence - Salim Al-Huseini; Mohammed Al Alawi; Naser Al-Balushi; Hamed Al Sinawi; Hassan Mirza; Rola Al Balushi; Manal Al Balushi; Sachin Jose; Angie Cucchi; Nasser Al-Sibani; Samir Al-Adawi; Nagina Khan (BJPsych International)
Previous research has focused on the significance of occupational burnout and the role of emotional intelligence and poor coping abilities among physicians.